2020
DOI: 10.3201/eid2608.201776
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Outcomes of Coronavirus Disease Patients under Nonsurge Conditions, Northern California, USA, March–April 2020

Abstract: Limited data are available on the clinical presentation and outcomes of coronavirus disease (COVID-19) patients in the United States hospitalized under normal-caseload or nonsurge conditions. We retrospectively studied 72 consecutive adult patients hospitalized with COVID-19 in 2 hospitals in the San Francisco Bay area, California, USA, during March 13–April 11, 2020. The death rate for all hospitalized COVID-19 patients was 8.3%, and median length of hospitalization was 7.5 days. Of the 21 (29% of total) inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
85
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(95 citation statements)
references
References 14 publications
9
85
1
Order By: Relevance
“…One study reported both adult and paediatric populations: only data from adult patients were included in this analysis [11]. Two further articles were found by manual searching, resulting in 24 articles for analysis [11–34] (Table 1, Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…One study reported both adult and paediatric populations: only data from adult patients were included in this analysis [11]. Two further articles were found by manual searching, resulting in 24 articles for analysis [11–34] (Table 1, Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Those with chronic medical conditions are known to have longer symptom duration, higher rates of ICU admission, increased development of ARDS, and elevated risk of death (Bhatraju et al., 2020; Tian et al., 2020; To et al., 2020; Wang, Yang, Li, Wen, & Zhang, 2020). Specifically, those with hypertension, cardiovascular disease, cerebrovascular disease, diabetes, and malignancy are at particular risk for ICU admission and fatal outcomes with COVID‐19 (Chen, Yang, et al, 2020; Chen, Sang, et al, 2020; Chen, Yang, et al, 2020; Feng et al., 2020; Ferguson et al, 2020; He et al., 2020; Liu, Jin, et al, 2020; Shi, Zhang, et al, 2020; Stroppa et al., 2020; Wang, He, et al, 2020; Wang, Du, & Zhu, 2020; Zhang, Zhu, et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The incidence of AKI in ICU patients with the COVID-19 was particularly high range from 8%-62% 15,18,[23][24][25]28,29 . Critical ill patients hospitalized with COVID-19, requiring ventilator is more likely to develop AKI 4 .…”
Section: Discussionmentioning
confidence: 98%
“…Overall, COVID-19 patients were included in our meta-analysis. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] The pooled estimated incidence of AKI in all hospitalized COVID-19 patients was 12.0% (95% CI: 9.0%-15.0%, Fig. 2), and a signi cant heterogeneity (I 2 = 98%, Chi-square = 0.19, P < 0.01) was observed ( Table 3).…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%